The HyVac4 Subunit Vaccine Efficiently Boosts BCG-Primed Anti-Mycobacterial Protective Immunity - Billeskov, Rolf (Public Library of Science, 2012)
BACKGROUND: The current vaccine against tuberculosis (TB), BCG, has failed to control TB worldwide and the protective efficacy is moreover limited to 10–15 years. A vaccine that could efficiently boost a BCG-induced immune response and thus prolong protective immunity would therefore have a significant impact on the global TB-burden. METHODS/FINDINGS: In the present study we show that the fusion protein HyVac4 (H4), consisting of the mycobacterial antigens Ag85B and TB10.4, given in the adjuvant IC31® or DDA/MPL effectively boosted and prolonged immunity induced by BCG, leading to improved protection against infection with virulent M. tuberculosis (M.tb). Increased protection correlated with an increased percentage of TB10.4 specific IFNγ/TNFα/IL-2 or TNFα/IL-2 producing CD4 T cells at the site of infection. Moreover, this vaccine strategy did not compromise the use of ESAT-6 as an accurate correlate of disease development/vaccine efficacy. Indeed both CD4 and CD8 ESAT-6 specific T cells showed significant correlation with bacterial levels. CONCLUSIONS/SIGNIFICANCE: H4-IC31® can efficiently boost BCG-primed immunity leading to an increased protective anti-M.tb immune response dominated by IFNγ/TNFα/IL-2 or TNFα/IL2 producing CD4 T cells. H4 in the CD4 T cell inducing adjuvant IC31® is presently in clinical trials.